2015
DOI: 10.1186/s40200-015-0143-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Therapeutic stimulation of GLP-1 and GIP protein with DPP-4 inhibitors for type-2 diabetes treatment

Abstract: Dipeptidyl peptidase-4 (DPP-4) inhibition is a new treatment for type-2 diabetes. DPP-4 inhibition increases levels of active GLP-1. GLP-1 enhances insulin secretion and diminishes glucagon secretion, in this manner reducing glucose concentrations in blood. A number of DPP-4 inhibitors are under clinical development. However, the durability and long-term safety of DPP-4 inhibition remain to be established. These synthetic DPP-4 inhibitors are showing some side effects. Herbal medicines are alternative medicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 99 publications
0
11
0
1
Order By: Relevance
“…When endogenous glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) levels are increased, DPP-4 inhibitors promote insulin release from islet β cells and inhibit glucagon secretion from islet α cells to decrease the blood glucose level [ 35 ]. It has been reported that DPP-4Is might exert some of their effects on insulin secretion by preserving intact GLP-1 and GIP secreted from alpha cells, although the insulinotropic effect of GIP has been shown to be reduced in patients with type 2 diabetes [ 36 38 ]. Several studies have found no definitive evidence supporting the cardiovascular benefits of DPP-4 inhibitors or TZDs [ 39 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…When endogenous glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) levels are increased, DPP-4 inhibitors promote insulin release from islet β cells and inhibit glucagon secretion from islet α cells to decrease the blood glucose level [ 35 ]. It has been reported that DPP-4Is might exert some of their effects on insulin secretion by preserving intact GLP-1 and GIP secreted from alpha cells, although the insulinotropic effect of GIP has been shown to be reduced in patients with type 2 diabetes [ 36 38 ]. Several studies have found no definitive evidence supporting the cardiovascular benefits of DPP-4 inhibitors or TZDs [ 39 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies of oral glucose tolerance test on animals showed that genetic deletion of DPP-IV have improved glucose tolerance and increased the insulin secretion [5] . In the other hand, the complete data of long term use of synthetic drugs of DPP-IV inhibitor have not been obtained yet, especially on its safety [6] . It induces the research of DPP-IV inhibitor compounds from herbs that are of less side effects, cheaper and easier to get.…”
Section: Introductionmentioning
confidence: 95%
“…It stimulates pancreas to release insulin and maintain glucose hemostatic level without any hyperglycemia. In addition, GLP-1 is rapidly degraded by the enzyme DPP-4 and it is no longer available in active form (17). In DM patients, the GLP1 level is reduced and the DPP4 level is increased and this in turn will cause the glucose hemostatic imbalance.…”
Section: Introductionmentioning
confidence: 99%